The Paradox Of Inter-Sectoral Coordination In Coastal Food Security: A Multi-Stakeholder Network Analysis In Majene Regency, Indonesia - Saddam Husain Tamrin; Novayanti Sopia Rukmana S; Bulkis Bulkis; Syarinullah Syahrinullah; Febrianto Syam (Universitas Sultan Ageng Tirtayasa, 2026)
This research highlights the coordination paradox in food security in Majene Regency. While the region boasts abundant natural resources, particularly in the maritime and agricultural sectors, institutional coordination remains fragmented. Formal institutions, such as the Food Security Council, have been inactive since 2021. To understand this issue, the research involved in-depth interviews with 15 key stakeholders from five government agencies and community groups. Social network analysis was used to map relationships between actors and identify gaps that hinder food security governance. The results reveal a coordination paradox, where informal communication takes over the role of formal mechanisms. This creates a resilient but inefficient governance structure. These findings enrich institutional studies by offering a